A 3 mu m difference frequency laser source for probing hydrocarbon plasmas - van Helden, J; Hancock, G; Peverall, R; Ritchie, G (2011)
The practicality of a compact solid-state laser-based difference frequency generation system is demonstrated as a tool for probing hydrocarbon-based plasmas. The laser light of a cw Nd : YAG operating at 1064 nm and one of two distributed feedback diode lasers operating at 1560 and 1620 nm were mixed in a periodically poled lithium niobate crystal producing mid-infrared radiation at 3.35 and 3.1 μm for the detection of CH 4 and C 2H 6 at the first wavelength and C 2H 2 and C 2H 4 at the latter. The radiation was used to probe a rf capacitively coupled CH 4 plasma for a matrix of conditions, varying power (<180 W) and pressure (<1 Torr) in both direct absorption spectroscopy and wavelength modulation spectroscopy (WMS) experiments to achieve relatively high sensitivities while retaining accurate spectral information in the form of linewidths. A minimum detectable absorption coefficient α min of 2 × 10 -5 cm -1 was achieved for direct absorption spectroscopy which corresponds to a minimum detectable density for CH 4 of 1.7 × 10 12 cm -3 and an α min value of 2 × 10 -6 cm -1 was achieved for WMS measurements on C 2H 2. The depletion of CH 4 was measured to increase from 23% at 40 W to 40% at 180 W at a pressure of 0.84 Torr, and the depletion increased to 56% as the pressure decreased to 0.45 Torr. © 2011 IOP Publishing Ltd.